Telepractice, Telehealth, and Telemedicine: Acquiring Knowledge From Other Disciplines. - Cohn, Ellen R.; Cason, Jana (Perspectives of the ASHA Special Interest Groups, 2016)
Telepractice for speech-language pathology and audiology operates within a complex and dynamic environment that is beset with many influencers: state and federal regulations, state professional licensure boards, reimbursement policies, standards and guidelines, and the interests of powerful financial drivers. While much that is written about telepractice does not reference telemedicine-based standards and guidelines, the latter can provide valuable information. Knowledge of the aspirational practices of other healthcare professions will benefit speech-language pathologists (SLPs) and audiologists and is essential for practitioners who work as part of interdisciplinary teams. The aspirational practices of other professions can also be drawn upon when devising telepractice curricula for university programs.